Ensuring security of economic and informational interests of mining enterprises taking into account innovative technological trends - Mishchuk, Ievgeniia; Serdiuk, Olha; Bekhter, Lilija; Bondarenko, Olena (Eastern-European Journal of Enterprise Technologies, 2021)
It was revealed that mining enterprises are poorly focused on rapid introduction of innovative technologies and developments in line with modern technological trends. Conceptual approach to ensuring the security of economic and informational enterprises` interests with innovative technological trends has been developed. Developed approach, in contrast to existing ones, makes it possible to determine directions of ensuring security in current period from perspective of future. It has been substantiated that proposed approach has high scientific explanatory potential for revealing substantive factors that determine current and desired enterprises` economic and informational interests’ security state. Highlighting security of economic and informational interests as component which is one of the first is responding to integration of innovation and technology degree will help to improve entire enterprise`s economic security ensuring quality. It is proposed to use ratio indicator of IT capital value to sum of fixed and intangible assets as indicator of security state of enterprise`s economic and informational interests. Verification of this indicator has been implemented. It is shown that automation of verification makes it possible to exclude subjective decision factor. On basis of verified indicator, state of economic and informational interest’s security of mining enterprises was assessed. The value obtained at PrJSC Northern GZK is 1, which corresponds to very high security state. Estimated values at all enterprises in sample are 0 and so they correspond to catastrophic security state. Obtained results are important, since they allow to reasonably make management decisions regarding the directions of ensuring the economic and informational interests security of mining enterprises on basis of IT capital value increasing